2022
DOI: 10.3390/metabo12121287
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Impacts of Diurnal Temperature Range on Mortality and Cardiovascular Disease: A Nationwide Prospective Cohort Study

Abstract: Previous studies have documented the associations between short-term diurnal temperature range (DTR) exposure and cardiovascular disease (CVD) via time-series analyses. However, the long-term impacts of DTR through a population-based prospective cohort have not been elucidated thoroughly. This study aimed to quantify the longitudinal association of DTR exposure with all-cause mortality and CVD in a nationwide prospective cohort and, by extension, project future DTR changes across China under climate change. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…Our stratified analyses suggested that counties with lower levels of urbanization, a higher labor force ratio, and lower education levels seem to experience an increased risk of all-cause mortality linked to annual exposure to mean temperature and temperature variability. These findings align with previous findings [44,47,48]. For instance, Hu et al [47] explored the differences in temperature-mortality relationships between rural and urban regions of Zhejiang Province, China.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our stratified analyses suggested that counties with lower levels of urbanization, a higher labor force ratio, and lower education levels seem to experience an increased risk of all-cause mortality linked to annual exposure to mean temperature and temperature variability. These findings align with previous findings [44,47,48]. For instance, Hu et al [47] explored the differences in temperature-mortality relationships between rural and urban regions of Zhejiang Province, China.…”
Section: Discussionsupporting
confidence: 89%
“…In alignment with previous findings, our observations revealed a strong association between the DTR and all-cause mortality [41][42][43]. A national study conducted in China, for instance, demonstrated that a 1 • C increment in the DTR elevated the risks of allcause, cardiovascular, and stroke mortality by 13% (95% CI: 8%, 18%), 12% (95% CI: 7%, 18%), and 9% (95% CI: 2%, 16%), respectively, after adjustment for potential confounders at the individual and regional levels [44].…”
Section: Discussionmentioning
confidence: 99%
“…This present study was the first to assess the effect of TV on stroke onset by matching temperature variability to precise stroke onset timing. In line with previous regional and national studies, which demonstrated that high diurnal temperature range (DTR) was associated with hospital admission for ischemic stroke, and for every 1°C increase in DTR, the risk of stroke increased by 9% (2-16%) (16,17), we also found a positive correlation between temperature variability and stroke morbidity, with a 4.1% (1.9-6.3%) increase in ischemic stroke onset for every 1°C increase in TV 0-1 .…”
Section: Discussionsupporting
confidence: 90%
“…Increased DTR was reported to be a risk factor of many diseases based on epidemiological data 3 5 . Tang et al reported a significantly positive relationship between long-term DTR exposure and all-cause mortality, with a 13% higher risk of all-cause mortality based on a 1 °C increase in the DTR exposure 33 . In our study, we chose 10–25 °C for the mouse model, based on (1) the maximum mean DTR in all the cities included were 15.55 °C; (2) the mean daily maximum temperature is 21.6 °C, and the minimum is 11.9 °C.…”
Section: Discussionmentioning
confidence: 99%